At a Crossroads: The Senior Woman Administrator Designation - Smith, Allison; Taylor, Elizabeth; Siegele, Jessica; Hardin, Robin (Journal of Intercollegiate Sport, 2020)
The Senior Woman Administrator (SWA) designation was established by the NCAA to increase involvement of women in the management of collegiate athletics. However, research has found SWAs may not be afforded opportunities needed for further career advancement. This study explored the perceptions of NCAA Division I SWAs through role congruity theory. Interviews revealed two major themes: Unintended Consequences and Future of the Designation. Themes highlighted how the designation itself is problematic and accompanied with gender stereotypes. Furthermore, participants detailed the designation should be removed due to tokenism and marginalization. The women in the study believed the designation of SWA may limit ascension into leadership roles within collegiate athletics.